New method of measuring the degree of lumbar spine curvature in pregnant women - Jeanette Mitchell; Donnèe Ness; Sandra Whitelock (AOSIS, 1992)
There are very few studies which record measurements of the degree of lumbar spine curvature. This study reports a new method of measuring the angle of curvature of the lumbar spine in pregnant women, using photography. It is a simple, cost-effective and non-invasive method which can be used in the laboratory or the clinical situation. The study sample consisted of 13 healthy, middle-class, English-speaking, South African, Caucasian women, aged between 20 and 40 years, in the third trimester of pregnancy. A mean angle of 33,9 ±3,6 (SD) degrees, representing the degree of lumbar spine curvature, was obtained.